Employee Perception of Leaders' Transformational and Transactional Leadership Behavior: A Comparison Between High and Low Performance Estates at Kumpulan Ladang Perbadanan Kedah - Azizi, Ahmad (2011)
This study seeks to examine the manifestation and effects of transformational and transactional leadership across employees’ perception in Kumpulan Ladang- Ladang Perbadanan Kedah Sdn Bhd. It also aims to investigate whether or not the employees’ perception on transformational and transactional leadership outcomes are contributes to the performance of the plantation units. A total of 65 employees which is selected randomly 5 from each operation units rated their leaders’ behaviors and the behaviors they expect of their leaders. The selected sample are 5 respondents from each estate with composed of 13 estates that in production modes and makes a total number of 65 respondent. The 5 respondents were expected to represent the whole 107 population of plantation staffs in Kumpulan Ladang Perbadanan Kedah Sdn Bhd . A total of 62 usable questionnaires were returned, giving a response rate of 95 per cent. This study found that those leadership behaviors that perceived by the employees had no significance difference to the performance of the estate. On the other words there is no contribution to the performance of the estate than those superior that not practice the behaviors.